2021
DOI: 10.3390/nu13103414
|View full text |Cite
|
Sign up to set email alerts
|

YG-1 Extract Improves Acute Pulmonary Inflammation by Inducing Bronchodilation and Inhibiting Inflammatory Cytokines

Abstract: YG-1 extract used in this study is a mixture of Lonicera japonica, Arctic Fructus, and Scutellariae Radix. The present study was designed to investigate the effect of YG-1 extract on bronchodilatation (ex vivo) and acute bronchial and pulmonary inflammation relief (in vivo). Ex vivo: The bronchodilation reaction was confirmed by treatment with YG-1 concentration-accumulation (0.01, 0.03, 0.1, 0.3, and 1 mg/mL) in the bronchial tissue ring pre-contracted by acetylcholine (10 μM). As a result, YG-1 extract is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The results showed that YG-1 extract treatment reduced the prevalence of respiratory symptoms and the incidence of non-specific lung diseases. YG-1 treatment also improved acute bronchial and pulmonary inflammation, at least in part, by regulating the inflammasome signaling pathways (such as NLRP3/caspase-1) [3]. These results support further exploration of YG-1 extract as an effective natural product in developing therapeutics for respiratory diseases.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The results showed that YG-1 extract treatment reduced the prevalence of respiratory symptoms and the incidence of non-specific lung diseases. YG-1 treatment also improved acute bronchial and pulmonary inflammation, at least in part, by regulating the inflammasome signaling pathways (such as NLRP3/caspase-1) [3]. These results support further exploration of YG-1 extract as an effective natural product in developing therapeutics for respiratory diseases.…”
supporting
confidence: 64%
“…YG-1 extract is a mixture of three different plants, including Lonicera japonica, Arctii Fructus, and Scutel lariae radix. Kim and coworkers investigated the effect of different concentrations of YG-1 extract on bronchodilatation, as well as acute bronchial and pulmonary inflammation relief ex vivo and in vivo, respectively [3]. Ex vivo, YG-1 extract showed concentration-dependent bronchodilation effects in Sprague Dawley rats by upregulating cAMP (cyclic adenosine monophosphate) levels through the β2-AR (β2-adrenergic receptor)/PKA pathway [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchodilators and anti-inflammatory drugs, such as dexamethasone, are currently used in treating respiratory diseases, but they are accompanied by serious side effects, such as renal dysfunction and gastrointestinal disorders. Therefore, alternative medicines that use natural products with few side effects are needed ( Mahemuti et al, 2018 ; Kim et al, 2021 ). Natural products are important sources of new drugs against various pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-inflammatory activity has been discovered in a number of synthetic neolignans [ 36 ]. Scutellariae Radix is a popular ethnobotanical herb used to treat various ailments ranging from inflammation to nervous disorders [ 37 , 38 ]. As a consequence, aqueous extracts of S. baicalensis roots were investigated to discover anti-inflammatory compounds from traditional Chinese medicines, and the neolignan constituents were found to have strong anti-inflammatory activities [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%